(untitled) (The Peerian Journal, 2023)
This article examines the pedagogical dialogue and its specific aspects, its role in the modern educational system, the peculiarity of communication and cooperation between the teacher and students, which serve the development of students. In the course of the study, theoretical materials were used using the methods of comparative analysis, analysis and synthesis, the importance of communication based on understanding and explanation between the teacher and the student was scientifically and theoretically substantiated